Invasion Entertainment / Max Gospel Pesin... [et al.] - Pesin, Max Gospel; Kassim, Mohammed Faizy; Tompong, Mohd Fian (2013)
Invasion Entertainment is an entertainment and event planner company that provided range of services to assist people on planning their event right from the start to the end. We focus on concert and gig event, festival event, trade and exhibition, and dinner event which include annual dinner. Today's society is always busy with their packed schedule that they do not have time to plan a proper event. These include the government, students, local people, and the musician. Besides, lack of time and experience on event planning limits them from planning a proper and exciting event. That is why Invasion Entertainment is established, to turn even the simplest event to be a life-long memory. With variety of theme to be chosen from, we will let the customer to decide what they want their event to be like. Be it a big or small event, memorable or just for pleasure event, or even planned last minute, Invasion Entertainment will deliver the best services we could provide in the friendliest way for a reasonable price. Customers just have to pick a date and location and we will organize everything from the decoration to arrangement of catering, gift, logistic and so on. Whatever the purpose of the event is, we will make sure everything is organized accurately and meet the customers’ satisfaction. Such company has been in Kota Kinabalu, but most of them focusing on other type of events such as, wedding, convention, road shows and more. Different from them, we are focusing on particular events, because we seek to be the brand that is annually held at Sabah. We also cooperate with the other suppliers like hotels restaurants and tour operators in order to create a link to promote our services. Besides that, we also plan to cooperate with Sounds Tech Production as our main supplier.